Intellectual Property Rights for Agricultural Biotechnology: Options and Implications for Developing Countries - Wijk, Jeroen van; Cohen, Joel I.; Komen, John (International Service for National Agricultural Research, 1993)
Policymakers in developing countries responsible for national agricultural research are considering the implications of adopting intellectual property rights for biotechnology. The impetus for these deliberations comes from many factors, including the desire of developing countries to acquire and use new technologies in agricultural research, and the pressure exerted on developing countries in international negotiations to strengthen their intellectual property legislation. In this report, the introductory chapters summarize the increasing significance of intellectual property rights for agricultural biotechnology and current international trade- and development-related debates on IPR and developing-country responses to these issues. An analysis is then provided of the complexities, options and implications regarding intellectual property rights in relation to three national technology objectives: acquiring either public or proprietary biotechnologies, developing and protecting national innovations, and choices for technology transfer and licensing.